Dampak Pengiring dari suatu Pengembangan Perangkat Pembelajaran Matematika - Nur Fauziah Siregar (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2021)
This study aims to see the impact of the accompaniment of a mathematics learning device development. The learning tools are lesson plans and worksheets. The subjects in this study were class VII students of SMP Negeri 7 Padangsidimpuan, totaling 41 students. The instruments used are questionnaires, interviews with 5 students and document studies in the form of lesson plans and worksheets. The data analysis technique used was that all the data were edited, coded, and the data was entered into a table and then analyzed. The accompaniment impact obtained by adding interest and attracting students' attention is the highest position, namely 93% and making it easier to understand material concepts and develop mathematical abilities occupies the lowest position, namely 73%. The impact of the accompaniment obtained in the interview seen from the aspect of interest and attention seemed to increase the focus of learning, increase the enthusiasm for learning mathematics and make learning mathematics more fun. Independence in learning mathematics has an accompaniment effect in increasing the ability to think about problem solving procedures, dare to ask questions, and learn from various sources. Thinking skills have an accompaniment impact that students have the ability to take the essence of the subject matter. Activities and creativity have an accompaniment impact that students are more active in learning mathematics and more creative in solving mathematical problems. In the study of documentation seen from 3 aspects, namely planning, implementation and evaluation which shows that it is written systematically